2015
DOI: 10.1097/sap.0000000000000015
|View full text |Cite
|
Sign up to set email alerts
|

Expression Patterns of HIF-1α Under Hypoxia in Vascular Smooth Muscle Cells of Venous Malformations

Abstract: These results indicate that the high expression of HIF-1α in VM VSMCs under hypoxic conditions could be an important factor for stimulating downstream angiogenesis in VM. Furthermore, the results of this investigation could provide the basis for future studies of VM pathophysiology, and ultimately lead to the development of new therapeutic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The expression of hypoxia-regulated HIF-1α has been described to be altered along with time ( 34 , 35 ). Therefore, we detected the HIF-1α expression after 24, 48 and 72 h in the present study and observed a similar variation pattern of HIF-1α expression at those three time-points (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of hypoxia-regulated HIF-1α has been described to be altered along with time ( 34 , 35 ). Therefore, we detected the HIF-1α expression after 24, 48 and 72 h in the present study and observed a similar variation pattern of HIF-1α expression at those three time-points (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…1 The vessel wall of the dysplastic veins is thin and weak with the absence of smooth muscle cells 2 and abnormal expression of hypoxia-inducible factors. 3,4 The continuous expansion of abnormal veins may lead to the rupture of venous wall, the fusion of vein channels, and the formation of giant venous sinus. 5…”
Section: Introductionmentioning
confidence: 99%